2020
DOI: 10.3390/ijms21228877
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Radiation-Induced DNA Damage on cGAS-STING-Mediated Immune Responses to Cancer

Abstract: Radiotherapy is a major modality used to combat a wide range of cancers. Classical radiobiology principles categorize ionizing radiation (IR) as a direct cytocidal therapeutic agent against cancer; however, there is an emerging appreciation for additional antitumor immune responses generated by this modality. A more nuanced understanding of the immunological pathways induced by radiation could inform optimal therapeutic combinations to harness radiation-induced antitumor immunity and improve treatment outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 123 publications
4
87
0
Order By: Relevance
“…Radiation induces antitumor T cells, complementing the activity of ICI [ 38 , 39 ]. Radiation may also activate the antitumor immune response by triggering the stimulation of the interferon gene (STING)-mediated DNA sensing pathway [ 40 , 41 ]. Hou et al demonstrated that the deficiency of noncanonical NF- κ B promotes radiation-induced antitumor immunity by regulating the STING-mediated type I IFN expression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation induces antitumor T cells, complementing the activity of ICI [ 38 , 39 ]. Radiation may also activate the antitumor immune response by triggering the stimulation of the interferon gene (STING)-mediated DNA sensing pathway [ 40 , 41 ]. Hou et al demonstrated that the deficiency of noncanonical NF- κ B promotes radiation-induced antitumor immunity by regulating the STING-mediated type I IFN expression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their functions are phagocytosis, sterilization, secretion of inflammatory factors, and tumor suppression, which are important roles in the immune response. 21 Macrophages play an important role in non-specific immunity, and participate in in vivo anti-infection, anti-tumor, and immune regulation processes. The strength of the phagocytosis can affect immune function.…”
Section: Discussionmentioning
confidence: 99%
“…As also stated in the excellent recent review by Storozynsky and Hitt [ 465 ], IR-induced DNA damage plays a very important role in IR-induced cGAS-STING-mediated immune responses to cancer. In fact, cytosolic mtDNA and also nDNA are recognized by cytosolic proteins, i.e., so-called inflammasomes belonging to the innate immune system [ 59 ].…”
Section: Involvement Of Mitochondria In Innate and Adaptive Immune Responses After Irmentioning
confidence: 95%